QUALITY TEST OF SAPPAN WOOD (Caesalpinia sappan L.) EXTRACT TONER - Prasdiantika, Ricka; Saraswati, Nanda; Tolkhah, Ronal (Universitas Muhammadiyah Magelang, 2025)
The skin is the body's outermost organ that continuously interacts with the surrounding environment. Free radical exposure, unpredictable weather, and outdoor activities cause skin damage, necessitating the use of skincare products such as toners containing antioxidants. Natural antioxidants could be obtained from woody plants like sappanwood (Caesalpinia sappan L.). This research aimed to create a toner preparation from sappanwood extract and test the physical quality of the preparation. The quality tests conducted on the toner preparation included organoleptic, pH, homogeneity, and viscosity tests. The method used in this research was quantitative descriptive. The toner preparation was made in four variations of sappanwood extract concentrations: 0%, 1%, 2%, and 4%. The organoleptic test results showed that all four formulas had a liquid form and an oleum rosae scent. F0 was clear in color, FI was red, FII was dark red, and FIII was reddish-brown. The pH test results for F0, FI, FII, and FIII were 5.43±0.015, 5.16±0.006, 5.02±0.006, and 4.96±0.006, respectively. The homogeneity test results for all four formulas showed homogeneous results, with no coarse particles or clumps. The viscosity test results F0, FI, FII, and FIII were 3.17±0.058 cP, 3.67±0.058 cP, 3.83±0.058 cP, and 3.97±0.058 cP, respectively. The results of the organoleptic, pH, homogeneity, and viscosity tests indicated that the sappanwood extract toner preparation met the requirements for a skin-cleansing toner.